2021
DOI: 10.1136/bcr-2021-243217
|View full text |Cite
|
Sign up to set email alerts
|

Varicella caused by airborne transmission of a localised herpes zoster infection in a family

Abstract: Localised herpes zoster infections spread by direct contact with active skin lesion, but airborne transmission is rare. We report a case of varicella from airborne transmission of a localised herpes zoster infection in a family. The patient was a 15-year-old boy who had never been vaccinated against the varicella-zoster virus (VZV). He likely developed varicella from his father, whom the patient lived with. The patient’s father developed a localised herpes zoster infection 2 weeks prior. The patient’s varicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Studies have also shown that transmission can occur when the aerosolized virus enters via the respiratory tract or mucosal surface like conjunctiva [ 11 ]. Airborne route has previously been reported as a common mode of transmission in nosocomial as well as localized community outbreaks [ 12 , 13 ]. Both primary varicella infection and herpes zoster (shingles) can act as the source of infection [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that transmission can occur when the aerosolized virus enters via the respiratory tract or mucosal surface like conjunctiva [ 11 ]. Airborne route has previously been reported as a common mode of transmission in nosocomial as well as localized community outbreaks [ 12 , 13 ]. Both primary varicella infection and herpes zoster (shingles) can act as the source of infection [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several VZV family clusters have been reported ( 12 , 13 ). Different with previous cases that reported the development of varicella in children after exposure to herpes zoster patients, in our case, all the family members (two children and their parents) continuously develop varicella after the grandmother’s herpes zoster infection.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of varicella from persons with localized herpes zoster most commonly results from direct contact with skin lesions; however, airborne transmission from localized herpes zoster has also been documented in some cases ( 13 15 ). The first and most likely scenario of transmission in this family is that the girl was firstly infected by direct contact with skin lesion of the grandmother, as the grandmother took care of these two children and they usually slept together.…”
Section: Discussionmentioning
confidence: 99%
“…This is a reason why the varicella pandemic remains unsolved. Childhood is the most prevalent age for VZV infection, which can spread through contact, droplet, and airborne transmission [ 82 ].…”
Section: Varicella–zoster Virus (Vzv) Conjunctivitismentioning
confidence: 99%